2019
DOI: 10.1080/10807039.2018.1529552
|View full text |Cite
|
Sign up to set email alerts
|

Metals and arsenic in marine fish commercialized in the NE Brazil: Risk to human health

Abstract: Arsenic, cadmium, lead, and mercury in fish is the result of longterm biomagnification in the food chain and is of public concern, due to the toxicity they engender. The objective of this research was to determine the concentrations of arsenic, cadmium, lead, and mercury in 13 species of marine fish broadly commercialized in Aracaju, SE, Brazil and to evaluate the risks of fish consumption associated with these trace elements, using the Target Hazard Quotient (THQ). As, Cd, and Pb levels were measured with ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 75 publications
3
18
1
Order By: Relevance
“…Exposure to As through contaminated food can also lead to serious health effects, including cancer, melanosis, lung disease, hypertension and ischaemic heart disease [ 7 ]. Considering the harmful consequences that these chemicals have on human health, many scientific reports about the levels of toxic metals in a wide variety of fish species have been reported all over the world [ 8 , 9 , 10 , 11 , 12 ]. In Italy, where the annual per capita consumption of fish is one of the highest within EU countries, at 31.02 kg [ 13 ], the quantification of trace metals and the characterization of human exposure risks arising from fish consumption has been explicitly addressed in many studies [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to As through contaminated food can also lead to serious health effects, including cancer, melanosis, lung disease, hypertension and ischaemic heart disease [ 7 ]. Considering the harmful consequences that these chemicals have on human health, many scientific reports about the levels of toxic metals in a wide variety of fish species have been reported all over the world [ 8 , 9 , 10 , 11 , 12 ]. In Italy, where the annual per capita consumption of fish is one of the highest within EU countries, at 31.02 kg [ 13 ], the quantification of trace metals and the characterization of human exposure risks arising from fish consumption has been explicitly addressed in many studies [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding Cd and Hg, the health risks of exposure to cadmium are compounded by the relative incapacity of humans to excrete it. Also, several studies revealed that MeHg constitutes the major Hg form present in fish and that MeHg is the most poisonous form of Hg (Micheline et al, 2019;Silva et al, 2020). In the present study, assuming that Hg is in the form of MeHg the EWIs values for both Cd and Hg through all fish species consumption by all consumers are exceeding the (PTWIs) and (TWIs) established by JECFA and EFSA.…”
Section: Health Risk Assessmentmentioning
confidence: 45%
“…Where, EF is the exposure frequency of the population (365 day/ year); ED is the exposure duration (30 years); FIR is the fish ingestion rate (59.29 g/day) (GAFRD, 2016). MC is the heavy metal concentration in the muscle tissue (μg/g), RFD represents the oral reference dose (μg/g/day) (Pb ¼ 4 Â 10 À3 , Cd ¼ 1 Â 10 À3 , As ¼ 0.3 Â 10 À3 , Hg ¼ 0.5 Â 10 À3 and Al ¼ 1) (USEPA, 2010; Jooste et al, 2014;Silva et al, 2020). BW is the average body weight (an adult: 70 kg); AT is the average time of non-carcinogenic exposure (365 day/yearÂED).…”
Section: Determination Of the Non-carcinogenic Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the National Health Surveillance Agency (ANVISA) (ANVISA, 2013), considering the risks of the consumption of mercury-contaminated fish and aiming to protect public health, has set a maximum limit of 0.5 μg g -1 Hg in non-predatory fish and 1.0 μg g -1 in predatory fish. In the Amazon, several studies have used mercury concentrations in hair as a biomarker to evaluate human exposure to this contaminant, mainly due to the diet composed of high fish intake (Pinheiro et al, 2006;Lima et al, 2015;Costa Júnior et al, 2015;Silva et al, 2020;Zampieri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%